2009 International Semiconductor Device Research Symposium 2009
DOI: 10.1109/isdrs.2009.5378036
|View full text |Cite
|
Sign up to set email alerts
|

On-state current stress-induced subthreshold I–V instability in SiC DMOSFETs

Abstract: The reliability of SiC DMOSFETs has been studied in the past several years, including gate oxide reliability with time-dependent dielectric breakdown measurements [1][2], and threshold voltage stability with gate-bias and On-state current stress measurements [2][3][4]. For example, it has been reported that gate-bias stressing causes a time-dependent shift in threshold voltage, and that an On-state current stress causes a slightly larger thresholdvoltage instability [4]. Furthermore, it has been observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…After the inversion of SiC MOSFETs, the influence of the onstate current stress on instability should be considered, and gate bias stress must exist if on-current stress is present. Lelis et al [53,54] reported that V th instability caused by the joint on-current and gate bias stress is greater than that induced by gate bias stress alone, but this difference is not significant. Usually, an on-current stress of 1 h likely causes an onstate conduction loss of about 7%.…”
Section: On-state Current Stressmentioning
confidence: 98%
See 1 more Smart Citation
“…After the inversion of SiC MOSFETs, the influence of the onstate current stress on instability should be considered, and gate bias stress must exist if on-current stress is present. Lelis et al [53,54] reported that V th instability caused by the joint on-current and gate bias stress is greater than that induced by gate bias stress alone, but this difference is not significant. Usually, an on-current stress of 1 h likely causes an onstate conduction loss of about 7%.…”
Section: On-state Current Stressmentioning
confidence: 98%
“…By contrast, traps near the SiC/SiO 2 interface that can exchange charges with substrates are also called border traps in oxides or NIOTs [63]. These NIOTs in oxides are the main charge-trapping active defects that result in V th instability, which is attributed to the charge and discharge of NIOTs or a carrier's tunneling into and out of NIOTs [23,24,50,53,54]. Therefore, studies have focused on NIOT-induced V th instability.…”
Section: Oxide Trapsmentioning
confidence: 99%